Gender Differences in Work Performance on the Baltimore Therapeutic Equipment Work Simulator. - Esmail, S.; Bhambhani, Y.; Brintnell, S. (American Journal of Occupational Therapy, 1995)
Objectives. The purposes of this study were to (a) establish biomechanical and physiological normative data for healthy young women performing three tasks on the Baltimore Therapeutic Equipment work simulator (BTE): wheel-turn, push-pull, and overhead-reach; and h) compare these data with previously reported values for healthy men of a similar age group. Method. Twenty women completed five test sessions: (a) task familiarization on the BTE to determine the work intensity that was perceived as hard on the Borg scale, (b) incremental test on an arm crank ergometer to measure peak oxygen uptake (O2) and peak heart rate (HR), and (c) one of the three tasks in random order for 4 min during the next three sessions. Physiological responses were monitored with a metabolic cart interfaced with an electrocardiogram. Results. Torque, work, and power during the three tasks were significantly higher (p < .05) in men than in women. The absolute O2 (L. mm-1 ) during these tasks was higher in men, but when the O2 was calculated relative to body weight (ml.kg-1 .mm-1), no significant (p > .05) gender differences were observed. Computation of energy expenditure relative to body weight and power output indicated that women expended significantly (p < .05) more energy than men. No significant (p > .05) gender differences were observed for O2 and HR when the values were expressed as a percentage of their respective peaks. Conclusions: Findings indicated that (a) the functional work capacity is significantly lower in women than in men, (b) when are less efficient than men when the energy expenditure is expressed per unit of body weight and power output, and (c) the relative physiological stress in men and women is similar under these conditions.